Elements of Neo-Walrasian Economics A Survey - Negishi, Takashi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2014)
This book aims to explain to the readers the basic idea of the general equilibrium theory, which forms the core of the current mainstream economics called neoclassical school. To understand this theory is absolutely necessary, either to study further or to criticize the contemporary economic theories. The author not only explains traditional theories, but also makes clear the many problems which are still unsolved. As a text book or reference book for those students who are studying microeconomics for the first time, the author recommends the use of Chapter 1, Chapter 2 (except section 9), Chapter 3 (from section 1 to section 3, section 6, section 11), Chapter 4 (from section 1 to section 4), Chapter 5 (from section 1 to section 5, section 8), Chapter 6 (except sections 6 and 7), Chapter 7 (from section 1 to section 5), Chapter 8 (from section 1 to section 6) and Chapter 9 (sections 1, 4 and 7). For more advanced readers, the author recommends the remaining sections and the literature recommended in the last part of each chapter. Problems given at the end of each chapter allow readers to confirm understanding of the content of the chapter and suggest to the readers more advanced studies. Incidentally, the author tried to avoid the use of the advanced mathematics. Only elementary knowledge of differential calculus and linear algebra are required to read this book.
Introduction -- Firms and Production -- Households and Consumption -- Market Equilibrium (1) -- Market Equilibrium (2) -- Perfect and Imperfect Competition -- Optimal Allocation of Resources -- Market Failures -- Optimal Income Distribution -- Microeconomic Foundations of Macroeconomics.
Keywords: Economic theory; Microeconomics; Economic history; Economics; Management science; Economic Theory/Quantitative Economics/Mathematical Methods; Microeconomics; History of Economic Thought/Methodology.; Economics, general